Myc protein overexpression is a feature of progression and adverse prognosis in multiple myeloma. (28th September 2018) - Møller, Hanne E. H.; Preiss, Birgitte S.; Pedersen, Per; Østergaard, Brian; Frederiksen, Mikael; Abildgaard, Niels; Møller, Michael B.
Abstract: Objective: Prognostic and predictive markers in multiple myeloma are continuously explored because of the heterogeneity of the tumor biology. Myc protein is the final product from activating MYC oncogene, but the prognostic impact in multiple myeloma is not well described. Methods: In a population‐based cohort of 194 untreated, newly diagnosed patients with multiple myeloma, we assessed myc protein expression using CD138/myc immunohistochemical double stain and collected clinicopathological data. Results: Cases with myc protein expression ≥40% (myc HIGH ) had a median overall survival of 11 months compared to 48 months in cases of myc protein expression <40% (myc LOW ) ( P < 0.01). Myc HIGH was significantly correlated to R‐ISS, high proliferation index, high percentage of plasma cell in bone marrow, plasmablastic morphology, high calcium level, and abnormal karyotype. In multivariate survival analyses, myc HIGH was independently associated with inferior overall survival with a hazard ratio of 2.5. Conclusion: Our results indicate myc protein overexpression to be associated with advanced multiple myeloma and poor prognosis.